2007
DOI: 10.1159/000106375
|View full text |Cite
|
Sign up to set email alerts
|

Genital Anomalies in Klinefelter’s Syndrome

Abstract: Background/Aims: Klinefelter’s syndrome is characterized by progressive testicular failure causing aspermatogenesis and androgen deficiency. Klinefelter patients classically have complete male sex differentiation, and genital anomalies are generally not recognized as associated features of the syndrome. Methods: We reviewed the cases of Klinefelter’s syndrome with genitalia abnormalities from the Cambridge Disorders of Sex Development Database, and also reviewed previous case reports of genital anomalies assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…KS is the most common abnormality of sexual differentiation, and occurs in approximately 1 in 500 live births. KS is a form of primary testicular failure with testicular hypotrophy and elevated gonadotropin plasma levels, and it represents the most common form of male hypogonadism [27]. Ferlin et al reported that the prevalence of KS among infertile men is very high, up to 5% in severe oligozoospermia and 10% in azoospermia [28].…”
Section: Discussionmentioning
confidence: 99%
“…KS is the most common abnormality of sexual differentiation, and occurs in approximately 1 in 500 live births. KS is a form of primary testicular failure with testicular hypotrophy and elevated gonadotropin plasma levels, and it represents the most common form of male hypogonadism [27]. Ferlin et al reported that the prevalence of KS among infertile men is very high, up to 5% in severe oligozoospermia and 10% in azoospermia [28].…”
Section: Discussionmentioning
confidence: 99%
“…KS is the most common abnormality of sexual differentiation, and occurs in approximately 1 in 500 live births. KS is a form of primary testicular failure with testicular hypotrophy and elevated gonadotropin plasma levels, and it represents the most common form of male hypogonadism [21]. Ferlin et al reported that the prevalence of KS among infertile men is very high, up to 5% in severe oligozoospermia and 10% in azoospermia [22].…”
Section: Discussionmentioning
confidence: 99%
“…5 There are few reported cases and they vary from penile chordee, hypospadias, and penoscrotal transposition. We reviewed the literature for patients diagnosed with Klinefelter syndrome before puberty with penoscrotal malformations; we searched PubMed using key words: Klinefelter syndrome, hypospadias, prepubertal age, chordee, bifid scrotum, and scrotal transposition (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In addition, 3 cases were excluded from a report due to the presence of ovary, ovotestes or atypical Karyotype. 5 Finally, we collected 15 patients, including our current case.…”
Section: Discussionmentioning
confidence: 99%